P849 Exposure to metals and minerals in hair samples of patients with preclinical inflammatory bowel disease. (30th January 2023) - Rodríguez-Lago, I; Rodríguez, A; Elorza, A; Sampedro, B; Jiménez, I; Erdozáin, I; Rodríguez, P; Fraga, A; De Castro, L; Oyón, D; Huerta, A; Carmona, M; et al.
Abstract: Background: Previous data have shown that the inflammatory process underlying ulcerative colitis (UC) and Crohn's disease (CD) can start years before the diagnosis, but the role of triggering factors and environmental exposures is still unknown. Hair element analysis is a valuable and inexpensive screen for physiological excess or deficiency of certain elements. Our aim was to determine if patients with an incidental diagnosis of UC or CD demonstrate exposure of minerals or toxic metals in the years preceding the symptomatic onset of the disease. Methods: We performed a prospective single-center study including all asymptomatic subjects with a diagnosis of UC or CD during the colorectal cancer screening program between January 2021 – June 2022 in Vizcaya (Basque Country, Spain). The diagnosis of IBD was established by a combination of clinical data, endoscopic findings suggestive of UC or CD, and after histologic confirmation. Cases were compared with a healthy non-IBD control population. An approximate hair sample of 0.25 g was obtained up to 3 months since diagnosis. We used a commercial kit that allows the investigation of 17 metals (Al, Sb, As, Ba, Be, Bi, Cd, Pb, Hg, Pt, Tl, Th, U, Ni, Ag, Sn, Ti) and 22 minerals (Ca, Mg, Na, K, Cu, Zn, Mn, Cr, V, Mo, B, I, Li, P, Se, Sr, S, Co, Fe, Ge, Rb, Zr). Descriptive statistics and non-parametric tests were used for comparisons between both groups. Results: Three patients with preclinical IBD were included (median age 53 years; 67% male; all former smokers). Two of them had a diagnosis of UC (one left-sided colitis and one extensive colitis) and one with ileal CD. Extraintestinal manifestations were observed in one patient (33%). No family history of IBD was reported. Thirteen healthy controls with no relevant environmental exposures (median age 34 years; 69% female; 92% non-smokers). We found that cases demonstrated statistically significant higher concentrations of bismuth, sodium and boron compared to controls (Figure). In contrast, there was a lower exposure to uranium, zinc and germanium, with a trend towards lower copper levels among cases. Conclusion: A range of environmental exposures can be identified during the preclinical phase of IBD. However, their relationship with the symptomatic onset and disease progression should be further explored.